1977
DOI: 10.1152/jappl.1977.43.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of diaphragmatic EMG response to CO2 rebreathing in humans

Abstract: To determine a reliable quantitative method of measuring diaphragmatic EMG (EMGdi), electrical activity of the diaphragm was obtained via an esophageal electrode during CO2 rebreathing in 6 normal males and processed three different ways: 1) integration (area), 2) as a moving time average, and 3) as a moving time variance. Integrated activity was quantified in terms of total activity and inspiratory activity. In addition, average total activity and average inspiratory activity were calculated. Moving average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 0 publications
1
44
0
1
Order By: Relevance
“…The stability of the EMG, despite changes in lung volume, could also be physiologically and clinically important to assess respiratory neural output using oesophageal diaphragm EMG, which was frequently used in the 1970s [4,15,19] but less so after GANDEVIA and MCKENZIE [7] suggested in 1986 that the oesophageal diaphragm EMG could not accurately reflect respiratory neural drive because of the considerable influence of lung volume on the diaphragm CMAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of the EMG, despite changes in lung volume, could also be physiologically and clinically important to assess respiratory neural output using oesophageal diaphragm EMG, which was frequently used in the 1970s [4,15,19] but less so after GANDEVIA and MCKENZIE [7] suggested in 1986 that the oesophageal diaphragm EMG could not accurately reflect respiratory neural drive because of the considerable influence of lung volume on the diaphragm CMAP.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown a good correlation between the phrenic nerve neurogram and the diaphragm EMG [3]. The integrated EMG during voluntary breathing has been used to assess neural drive in humans [4]. However, accurate assessment of neural respiratory drive requires reliable recording of the diaphragm EMG that is not influenced by changes in lung volume.…”
mentioning
confidence: 99%
“…The diaphragmatic electromyogram has been used as an index of neural output of the respiratory centers during periods of heightened respiratory drive (14). The reliability of this index is dependent on 1) the position of the recording electrode relative to the diaphragm (1 5), 2) the electrical conductivity of the immediate environment of the costal diaphragm (1 6), and 3) the length-tension state of the diaphragm (1 7).…”
Section: Discussionmentioning
confidence: 99%
“…The EMG signal was processed further utilizing a Service Associates 414 analog processor where it was filtered to allow passage of frequencies between 30 and 3000 Hz. The EMG was full-wave rectified and integrated through a simple R-C filter ( T = 100 ms) to obtain moving average (14). The EMG and processed signals were displayed on a Tektronix 5 1 1 1A storage oscilloscope and a Gould four-channel chart recorder (Brush 440).…”
Section: Methodsmentioning
confidence: 99%
“…The EMG signal was processed using a Service Associates 4 14 analog processor (Encinitas, CA), where it was filtered to allow passage of frequencies between 30 and 3000 Hz. The EMG was full-wave rectified and integrated through a Paynter filter with a 100-ms time constant to obtain moving time average EMG (19). In addition, an ECG signal was monitored and recorded on the FM tape via two wire electrodes placed in the chest wall.…”
Section: Methodsmentioning
confidence: 99%